Incidence of early pregnancy bleeding in the Eastern region of Saudi Arabia - Hassan, Wafaa; Abu-Helalah, Munir; Salam, Abdul; Elhakim, Abdelmonim; Bayazeed, Honida; Latif, Shahid; Rehmani, Rifat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Early pregnancy bleeding (EPB) is defined as bleeding within the first 20 weeks of gestation. Women who present with bleeding in early pregnancy have 30 – 50% probability of having a failed pregnancy. Recent US statistics report that it accounts for 1.6% of all ED visits. Although first-trimester vaginal bleeding is an alarming symptom, there is limited published literature on its incidence, timing, and risk factors and there is no published data from the KSA. Methods: This retrospective cohort study included pregnant women who attended their first antenatal visit between August 2011 and May 2012. Results: The number of participants was 724 women who attended the antenatal clinic for first pregnancy visit. 37.85% of them (274) of developed first trimester vaginal bleeding. 62% experienced mild bleeding, 15.4% had moderate bleeding, 13.9% had spotting, while 4.9% of had severe bleeding. The incidence of threatened miscarriage was the highest (11.5%) followed by incomplete miscarriage (8.8%) and missed carriage (7.7%). The incidence of molar pregnancy in our study of 0.55% was very high. Conclusions: The incidence of first trimester vaginal bleeding is high in our center when compared with figures from published literature. The incidence of threatened miscarriage is low, while the incidence of complete or incomplete miscarriage is relatively high. Similar to other reports from Asia, the incidence of molar pregnancy was very high. Further research is recommended to justify the detected high first trimester vaginal bleeding rates and to identify potentials of prevention or improvement of the outcomes of bleeding.